Visual understanding and personalization for an optimal recollection experience - Ana, Garcia del Molino (2019)
The affordability of wearable cameras such as the Narrative Clip and GoPro allows mass-market consumers to continuously record their lives, producing large amounts of unstructured visual data. Moreover, users tend to record with their smartphones more multimedia content than they can possibly share or review. We use each of these devices for different purposes: action cameras for travels and adventures; our smartphones to capture on the spur of the moment; a lifelogging device to record unobtrusively all our daily life activities. As a result, the few important shots end up buried among many repetitive images or uninteresting long segments, requiring hours of manual analysis in order to, say, select highlights in a day or find the most aesthetic pictures.